2002
DOI: 10.1161/01.hyp.0000019129.44960.c0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Protein and Essential Hypertension in Black and in White People

Abstract: Abstract-The objectives of this work were to examine the association between urinary protein and blood pressure and to compare the pattern of urinary protein excretion with essential hypertension in people of European origin (whites) and in people of African or African-Caribbean origin (blacks) living in southwest London, United Kingdom. In the groups as a whole, there were no significant differences in total urinary protein excretion between blacks and whites (geometric means ). In both groups, those with ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
(28 reference statements)
2
17
0
2
Order By: Relevance
“…29 Only few studies have been carried out on the association of transferrinuria and elevated blood pressure in nondiabetic hypertensive patients and report no 23 or a weak (r ¼ 0.51 for systolic and r ¼ 0.36 for diastolic blood pressure) correlation. 30 Our study confirms these findings, we found a weak (ro0.20) correlation between TCR and OBP or mean 24-h blood pressure. Other factors as dysfunction of intraglomerular haemodynamics or changes in permeability of the glomerular membrane may be more important determinants for the development of transferrinuria.…”
Section: Discussionsupporting
confidence: 89%
“…29 Only few studies have been carried out on the association of transferrinuria and elevated blood pressure in nondiabetic hypertensive patients and report no 23 or a weak (r ¼ 0.51 for systolic and r ¼ 0.36 for diastolic blood pressure) correlation. 30 Our study confirms these findings, we found a weak (ro0.20) correlation between TCR and OBP or mean 24-h blood pressure. Other factors as dysfunction of intraglomerular haemodynamics or changes in permeability of the glomerular membrane may be more important determinants for the development of transferrinuria.…”
Section: Discussionsupporting
confidence: 89%
“…3,4,[7][8][9][10] In the GPRD, we also found a low prevalence of recording for other cardiovascular risk factors. In UK general practice, screening for the presence of diabetes 33 and proteinuria 34 is not routinely performed. Similarly, echocardiographs are only advocated in patients suspected of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Эта дисфункция присутствует в патогенезе АГ вне зависимости от уровня АД [34]. Общепринятыми показателями оценки степени почечного органного поражения, вследствие повсед-невного потребления соли, являются показатели кли-ренса креатинина, альбуминурии, в том числе микро-альбуминурии [36,39]. Микроальбуминурия -обще-принятый маркер начального повреждения почечной ткани -предлагается как дешевый тест для скри-нинга сердечно-сосудистых рисков [37].…”
Section: Salt Consumption кIdneys As the Target Organ рArt IVunclassified
“…Микроальбуминурия -обще-принятый маркер начального повреждения почечной ткани -предлагается как дешевый тест для скри-нинга сердечно-сосудистых рисков [37]. Она корре-лирует с ростом смертности как от ССЗ [36][37][38]43], так и от некардиальных причин [38] даже у здоровых лиц [38,39]. По предложенной в XX веке гипотезе (Stenohypothesis) микроальбуминурия -отражение поражения сосудистого ложа почек и системной эндотелиальной дисфункции [40].…”
Section: Salt Consumption кIdneys As the Target Organ рArt IVunclassified